1642a Building prevention-oriented team support for good occupational health practices in developing countries. (24th April 2018) - Kogi, K; Sano, Y
Abstract : Introduction: In globalising economies, occupational health teams increasingly focus on locally adjusted support functions known as basic occupational health services. Networked collaboration in Asian countries indicate the importance of facilitating primary prevention of work-related risks through participatory steps leading to multifaceted workplace environment improvements. It is useful to know practical ways for developing countries to facilitate implementation of these improvements through locally adjusted risk management procedures. Methods: Recent experiences of occupational health teams within our Asian network for promoting participatory workplace improvement programs are examined. The reviewed programs aim at improving workplace environment in small enterprises, construction sites, agriculture and health care work. To know commonly effective procedures, we focus on solution-oriented procedures of addressing multifaceted risks usually identified in developing countries. Results: In the reviewed participatory programs, concrete results are usually obtained when the programs emphasise feasible low-cost improvements reflecting broad-ranging local good practices. This good-practice approach is effective when occupational health support teams focus on multifaceted improvements having real impacts on primary prevention of work-related risks. Typically, these improvements have a broad scope covering work methods, physical environment and teamwork arrangements. As means of facilitating the planning of risk-reducing improvements, broadly compiled good practices and 'action checklists' listing corresponding low-cost improvements have proven useful. Intervention studies on applying these participatory methods indicate actual reduction of multiple risks. The simplified solution-oriented procedures relying on group work of workers about feasible actions thus represent the core function of occupational health teams in facilitating primary prevention of work-related health risks. Conclusions: The solution-oriented support of occupational health teams directly aimed at locally feasible preventive measures is found essential, rather than detailed analysis of risk factors. Simplified participatory procedures are confirmed useful in facilitating primary prevention of multifaceted health hazards at workplaces in developing countries.